Designing of innovative mining equipment for safe and successful work in mines; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Trifonov V. A. Vladimir Aleksandrovich (2016, 2016)
Title screen